Estratégias de mediação do sofrimento no trabalho: uma análise sobre a aceleração e os efeitos na subjetividade do trabalhador - CARVALHO, Ana Flavia Moura (2018)
The work category has become more central to humanity after the industrial revolution in capitalism, and its importance has shown to be crucial for understanding its impacts on worker‘s subjectivity. The expansion of the capitalist model in the second half of the twentieth century has caused a progressive increase in time and uninterrupted dedication to work and employment, which has results on worker‘s health. As a result of the productive restructuring, new work/employment configurations marked by instability, flexibility and loss of social rights and guarantees, present themselves as outstanding characteristics of this new scenario. With the intensification of the productive process and the permanent search for an increase in productivity, employment also starts to occupy the free time of work, leading this worker to do work activities at home; to participate of professional formation and qualification activities; to rest to recover the work force or consume increasingly more, in order to promote the realization of capital, among other activities. The effects of this precariousness of work have repercussions on the subjectivity of the contemporary worker, with each subject expressing itself in a unique way. This paper aims to analyze the impacts of work on worker‘s subjectivity, emphasizing the psychological suffering as a result of this relationship, starting from the analysis of the work category in modernity and how psychic suffering is manifested from the relation man-work, describing the diverse devices used as individual and collective defensive strategies in confronting to the psychological suffering up until the work is done. The research adopted the qualitative method, through a literature review in books and productions in the main scientific databases, using as theoretical reference the Psychodynamics of Work and Sociology of Work.